Analysing the efficiency of digital payment applications in Davangere District - Bhoote, Megha; Muralidhar, S. (The International tax journal, 2026)
In India the most widely adopted digital payment system is Unified Payment Interface (UPI), which enable the seamless and instant fund transfer through the mobile based applications. UPI services are offered in two ways i.e. bank specific applications and third party UPI applications. Both the apps are differing in design, service delivery and operational efficiency. There is the rapid growth in UPI usage, both the apps are experience the various challenges which influence the efficiency and overall performance of these applications. The main purpose is to compare the challenges faced by the apps, improvements required for both the apps and resolving mechanism of bank specific app and third party UPI app. The study is based on both primary and secondary data. Primary data were collected from 118 respondents using the structure questionnaire. Statistical tools such as percentage analysis, weighted average mean and chi-square test were used to analyse and interpret the data. The findings of the study reveals that both the bank specific and third party UPI apps face the challenges such as transaction failures, security concern, network issues, complex user interface and limited merchant acceptance.